Cultural y corresponded, interpersonal and spiritual Communication in the educational process - Stasyuk, Tetyana; Стасюк, Тетяна Валеріївна (Дніпровський державний аграрно-економічний університет, 2023)
The purpose of the study is to analyze the principles of organizing the educational process in the key of culturally corresponded, interpersonal and spiritual communication, to describe the effectiveness of upbringing, education and teaching by observing the basic requirements for the favorable development of the individual. Метою дослідження є аналіз принципів організації освітнього процесу в ключі культуро-відповідного, міжособистісного та духовного спілкування, охарактеризувати ефективність виховання, навчання та навчання шляхом спостереження.
Культуро-відповідне, міжособистісне та духовне спілкування в освітньому процесі
Keywords: educational environment; освітнє середовище; pedagogical influence; педагогічний вплив; pedagogical ideal; педагогічний ідеал; upbringing; виховання